Pemanfaatan Koleksi Khusus Muatan Lokal Oleh Pemustaka Di UPT Perpustakaan Proklamator Bung Hatta Kota Bukittinggi - Fadhil, Al Fauzan; Marlini, Marlini (JURNAL PENDIDIKAN ROKANIA, 2023)
User satisfaction is an important thing for the UPT Bung Hatta Proclaimer Library, Bukittinggi City. One indicator that can increase user satisfaction is the existence of a collection of local content that can add information about culture, especially local culture in Bukittinggi, but based on the results of interviews and initial observations there are still users who find it difficult to utilize the collection of local content. This study aims to describe the use of local content collections at the Bung Hatta Proclaimer Library UPT Bukittinggi City. This research is a type of quantitative research with descriptive method. The population in this study was taken from users who visited the local content collection located in the reference collection with a total of 131 people. Sampling used a random sampling technique, namely random sampling of 57 samples. Data analysis was carried out descriptively with the formula of relative frequency and percentage. The results showed that the use of local content collections at the Bung Hatta Proclaimer Library in Bukittinggi City was said to be able to meet the information needs of users in the medium category. Measured by indicators of collection utilization. Based on the results obtained, it shows a medium category with a score of 3.01 which is on an interval scale of 2.61 - 3.40 in the medium category with the smallest indicator of 2.96 and the highest indicator of 3.13.